Characterization of rotor losses in permanent magnet machines. Issue 5 (27th July 2020) - Caunes, Antomne; Takorabet, Noureddine; Chaithongsuk, Sisuda; Duranton, Laurent
Abstract : Purpose: The purpose of this paper is to present a synthesis of the analysis and modeling of the rotor losses in high speed permanent magnets motors. Design/methodology/approach: Three types of losses are as a result of eddy currents in the conductive parts of the rotor. The analysis includes their characterization and the setup of a numerical model using finite element method. The adopted methodology is based on the separation of the losses which allows a better understanding of the physical phenomena. Each type of losses will be modeled and computed separately. Findings: It is possible to make a precise estimate of the different losses in the rotor while keeping a relatively short computing time. Research limitations/implications: The analysis is applied on a high-speed permanent magnet motor for avionic application. The model is validated with the commercial finite element model (FEM) software Flux2D. Originality/value: The developed model allows an important save in terms of CPU-time compared to commercial FEM software while staying accurate. The separation of each losses and their sources is important for motor engineers and was requested for them to improve the designs more easily.